High Risk Human Papillomavirus & Risk Factors for Cervical Cancer - Agustini, Riani; Yasmon, Andi (Jurnal Ners, 2024)
Cervical cancer is caused by the non-enveloped, Papillomavirus, or HPV, is an example of a double-stranded DNA virus.. According to the 2020 Global Cancer Observatory (GLOBOCAN) survey, a global study of female populations, cervical cancer is associated with a relatively high fatality rate. Cervical cancer is the second most prevalent form of the disease among women in Indonesia. Over 73% of instances of cervical cancer are known to be caused by high-risk HPV strains 16 and 18. The proteins E6 and E7 significantly prevent the tumor suppressors p53 and pRb from acting, which would otherwise cause cells to proliferate and become uncontrollably large. It is necessary to identify the risk factors that lead to cervical cancer in order to take the necessary preventive action.